Tugas Dinas Pariwisata Dalam Pengelolaan Pembangunan Kepariwisataan Daerah Kabupaten Ende Berdasarkan Peraturan Daerah Kabupaten Ende Nomor 7 Tahun 2016 Tentang Rencana Induk Pembangunan Kepariwisataan Daerah Kabupaten Ende - Mario Hardi Kusuma (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2022)
The purpose of this research is to find out and analyze the effectiveness of the Tourism Office's duties in managing tourism development in Ende Regency and to find out the factors that hinder the management of tourism development in Ende Regency. The use of this research is as a contribution to the body of legal science, especially constitutional law and as the development of constitutional law knowledge, especially regarding the management of tourism development and as material for academic studies in the field of law. In order to answer these problems, research was carried out using the Qualitative Descriptive Analysis method in accordance with the data obtained while still paying attention to theory, principles and legal principles, so this research is research that originates from primary and secondary data using an empirical juridical approach. That in the results of this study, the main issues examined by the researchers explain the implementation of the duties of the Tourism Office in managing tourism development, namely the Tourism Office of Ende Regency always strives to implement programs/activities every year to continue to increase both in quantity and quality so that services to the community can be fulfilled. In addition to encouraging/increasing public awareness in the field of tourism (tourism awareness), this effort is also a concern for poverty alleviation efforts, job creation, economic growth, as well as concern for environmental preservation and the factors that hinder the management of tourism development in Ende Regency, namely human resources, infrastructure and infrastructure, budget and legal awareness of the community. Based on the results of the research that has been done, the authors provide advice related to this problem: The researcher wants to increase the implementation of the duties of the Tourism Office in terms of managing tourism development in Ende Regency so that all tourist objects in Ende Regency can be known by local and foreign tourists and There is a need for the development of human resources in Ende Regency because human resources are an important element in the implementation of tourism development in Ende Regency, supporting facilities and infrastructure so that they can assist parties from the Tourism Office to help achieve the realization that their work programs are implemented properly. Keywords: Tourism Office; Management; Tourism Development.